2016
DOI: 10.1104/pp.16.00127
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Treatment Strongly Inhibits New Arbuscule Development But Not the Maintenance of Arbuscule in Mycorrhizal Rice Roots

Abstract: ORCID IDs: 0000-0002-9997-490X (Y.K.); 0000-0001-8867-5085 (C.S.).Phosphorus (P) is a crucial nutrient for plant growth, but its availability to roots is limited in soil. Arbuscular mycorrhizal (AM) symbiosis is a promising strategy for improving plant P acquisition. However, P fertilizer reduces fungal colonization (P inhibition) and compromises mycorrhizal P uptake, warranting studies on the mechanistic basis of P inhibition. In this study, early morphological changes in P inhibition were identified in rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 84 publications
3
55
0
1
Order By: Relevance
“…The nutritional status of the plant and surrounding environment, as well as Pi delivered through the AM symbiosis, affect AM symbiosis. However, the underlying mechanisms are mostly unknown (Koide and Schreiner, 1992;Breuillin et al, 2010;Hammer et al, 2011;Kiers et al, 2011;Kretzschmar et al, 2012;Yoneyama et al, 2012;Kobae et al, 2016). Transcriptomic analyses revealed that high levels of Pi repressed the expression of genes encoding carotenoid and strigolactone biosynthesis enzymes in plants, suggesting that high levels of Pi directly inhibit spore germination by reducing strigolactone biosynthesis.…”
Section: Regulation Of Nutrient Exchange By Pi and N In Am Symbiosismentioning
confidence: 99%
“…The nutritional status of the plant and surrounding environment, as well as Pi delivered through the AM symbiosis, affect AM symbiosis. However, the underlying mechanisms are mostly unknown (Koide and Schreiner, 1992;Breuillin et al, 2010;Hammer et al, 2011;Kiers et al, 2011;Kretzschmar et al, 2012;Yoneyama et al, 2012;Kobae et al, 2016). Transcriptomic analyses revealed that high levels of Pi repressed the expression of genes encoding carotenoid and strigolactone biosynthesis enzymes in plants, suggesting that high levels of Pi directly inhibit spore germination by reducing strigolactone biosynthesis.…”
Section: Regulation Of Nutrient Exchange By Pi and N In Am Symbiosismentioning
confidence: 99%
“…In addition to its cell-autonomous influence on arbuscule maintenance, Pi also regulates AM formation in a systemic manner. It has long been known that AM colonization is repressed when plants are grown under high Pi supply (Mosse, 1973;Branscheid et al, 2010;Balzergue et al, 2011;Kobae et al, 2016). In addition, in split-root experiments, in which only one side of the split root system was fertilized with high Pi concentrations, AM formation was suppressed on both sides (Branscheid et al, 2010;Breuillin et al, 2010;Balzergue et al, 2011).…”
Section: Phosphate Status Influences Am Developmentmentioning
confidence: 99%
“…As phospholipids potentially contain phosphate and lipids traded between symbionts, alterations in vesicle abundance may reflect major defects in symbiotic nutrient homeostasis. Unlike arbuscules, vesicle formation is stimulated by phosphate treatment in rice (Kobae et al ., ) suggesting them to have complex yet‐to‐be understood roles in the fungal handling of nutritional resources. Vesicles and spores are overlooked structures but they give account of the completion of fungal life cycle which is, in turn, relevant for subsequent recolonization.…”
Section: It Is Not Over When the Arbuscule Is Overmentioning
confidence: 99%